Quantifying antimicrobial use on Canadian dairy farms using garbage can audits - Warder, Landon M. C.; Heider, Luke C.; Léger, David F.; Rizzo, Daniella; McClure, J. T.; de Jong, Ellen; McCubbin, Kayley D.; Uyama, Tamaki; Fonseca, Mariana; Jaramillo, Ana Soffia; Kelton, David F.; Renaud, David; et al. (Frontiers in Veterinary Science, 2023)
Antimicrobial resistance in pathogenic bacteria is one of the preeminent concerns for the future of global health. There is a dose-dependent relationship between antimicrobial use (AMU) and the prevalence of antimicrobial-resistant pathogens. As most AMU in Canada is related to animal agriculture, there is a need to reduce overall AMU, which could be accomplished through surveillance of AMU in animal agriculture, including the dairy industry. The objective of this study was to quantify AMU on dairy farms across Canada. This study had two parts. The first included a garbage can audit (GCA) on 107 farms in four Canadian provinces (British Columbia, Alberta, Ontario, and Nova Scotia) in 2020; AMU data were converted to the dose-based metrics of defined course doses (DCD) and defined daily doses (DDD). Mixed-effect linear and logistic models were fit to determine the relationship between province and use of different classes of antimicrobials. On average, for every 100 animals on the farm, 117 DCD of antimicrobials were administered per year (IQR: 55, 158). These treatments amounted to 623 DDD / 100 animal-yr (IQR: 302, 677 DDD/100 animal-years). Penicillins were the most used class of antimicrobials, followed by first- and third-generation cephalosporins. Farms in Ontario used more third-generation cephalosporins than other provinces. The second part of this study compared AMU in 2020 to previously reported Canadian studies. A GCA was conducted in 2007-2008 in Alberta, Ontario, Québec, and the Maritime provinces (Prince Edward Island, New Brunswick and Nova Scotia); another GCA was conducted in Québec in 2018. Overall, AMU was lower in 2018-2020 than in 2007-2008, with the exception of third-generation cephalosporin use, which increased.